2005
DOI: 10.1007/s00204-005-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell death effects of resin-based dental material compounds and mercurials in human gingival fibroblasts

Abstract: In order to test the hypothesis that released dental restorative materials can reach toxic levels in human oral tissues, the cytotoxicities of the resin-based dental (co)monomers hydroxyethylmethacrylate (HEMA), triethyleneglycoldimethacrylate (TEGDMA), urethanedimethacrylate (UDMA), and bisglycidylmethacrylate (BisGMA) compared with methyl mercury chloride (MeHgCl) and the amalgam component mercuric chloride (HgCl2) were investigated on human gingival fibroblasts (HGF) using two different test systems: (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 51 publications
4
84
3
6
Order By: Relevance
“…This effect may be linked to the high molecular weight of Bis-GMA relative to ACR (Table 1), since in dental (co)monomers a direct correlation between increasing molecular weight and the degree of cytotoxicity has been observed 64,65) ( Table 1). HEMA and TEGDMA were up to 110-fold less toxic than Bis-GMA, whereas HEMA was less toxic than TEGDMA, in agreement to former own results 65) . This can be explained by the more hydrophilic character of HEMA, which has an additional hydroxyl group compared with TEGDMA.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be linked to the high molecular weight of Bis-GMA relative to ACR (Table 1), since in dental (co)monomers a direct correlation between increasing molecular weight and the degree of cytotoxicity has been observed 64,65) ( Table 1). HEMA and TEGDMA were up to 110-fold less toxic than Bis-GMA, whereas HEMA was less toxic than TEGDMA, in agreement to former own results 65) . This can be explained by the more hydrophilic character of HEMA, which has an additional hydroxyl group compared with TEGDMA.…”
Section: Discussionmentioning
confidence: 99%
“…Mohsen et al (34) determined that different aging procedures increased the biocompatibility of composites (42).…”
Section: Fig 2 Sem Images Of L929 Cells After the 3 Rd Day Of Incubmentioning
confidence: 99%
“…98 The study of Nakagawa has shown that the total mercury concentrations in the hair of ordinary diseased people, including diabetes, were from 2.08 to 36.5 ppm; those values were considerably higher than that of healthy people of the same age-groups. 99 Organic or inorganic mercury compounds are well known to induce cellular damage in various cell types, such as renal cells, 92 astrocytes, 100 lymphoma cells, 101 human gingival fibroblast cells, 102 alveolar epithelial cells 103 and pancreatic islet β-cells. 104 Except for organic and inorganic forms of mercury toxicity, many studies focus on the vaccine preservative-thimerosal.…”
Section: Mercurymentioning
confidence: 99%